Molecular Mechanisms of Tungsten Toxicity Differ for Glycine max Depending on Nitrogen Regime - Preiner, Julian; Wienkoop, Stefanie; Weckwerth, Wolfram; Oburger, Eva (Frontiers in Plant Science, 2019)
Tungsten (W) finds increasing application in military, aviation and household appliance industry, opening new paths into the environment. Since W shares certain chemical properties with the essential plant micronutrient molybdenum (Mo), it is proposed to inhibit enzymatic activity of molybdoenzymes [e.g., nitrate reductase (NR)] by replacing the Mo-ion bound to the co-factor. Recent studies suggest that W, much like other heavy metals, also exerts toxicity on its own. To create a comprehensive picture of tungsten stress, this study investigated the effects of W on growth and metabolism of soybean (Glycine max), depending on plant nitrogen regime [nitrate fed (N fed) vs. symbiotic N2 fixation (N fix)] by combining plant physiological data (biomass production, starch and nutrient content, N2 fixation, nitrate reductase activity) with root and nodule proteome data. Irrespective of N regime, NR activity and total N decreased with increasing W concentrations. Nodulation and therefore also N2 fixation strongly declined at high W concentrations, particularly in N fix plants. However, N2 fixation rate (g N fixed g−1 nodule dwt) remained unaffected by increasing W concentrations. Proteomic analysis revealed a strong decline in leghemoglobin and nitrogenase precursor levels (NifD), as well as an increase in abundance of proteins involved in secondary metabolism in N fix nodules. Taken together this indicates that, in contrast to the reported direct inhibition of NR, N2 fixation appears to be indirectly inhibited by a decrease in nitrogenase synthesis due to W induced changes in nodule oxygen levels of N fix plants. Besides N metabolism, plants exhibited a strong reduction of shoot (both N regimes) and root (N fed only) biomass, an imbalance in nutrient levels and a failure of carbon metabolic pathways accompanied by an accumulation of starch at high tungsten concentrations, independent of N-regime. Proteomic data (available via ProteomeXchange with identifier PXD010877) demonstrated that the response to high W concentrations was independent of nodule functionality and dominated by several peroxidases and other general stress related proteins. Based on an evaluation of several W responsive proteotypic peptides, we identified a set of protein markers of W stress and possible targets for improved stress tolerance.